Sikap Dengan Motivasi Dalam Memberikan Pertolongan Pertama Kasus Kecelakaan Lalu Lintas Pada Siswa Siswi SMK Negeri 1 Maumere - Irman, Ode (Journal Nursing Care and Biomolecular, 2019)
Traffic accidents are the main killers of young people aged 10-24 years. The students often find victims of traffic accidents but do not provide first aid because of a lack of attitude and motivation in helping. Lack of attitude and motivation in handling traffic accidents can result in the condition of the victim getting worse and leading to death. This study aims to explain the correlation attitudes and motivation in providing first aid traffic accidents to students at SMK Negeri 1 Maumere.  This type of research is correlation analysis. The study design was cross sectional. The sampling used was simple random sampling with a total sample of 75 people. Data were collected using a questionnaire and analyzed using the contingency coefficient test. The results showed that 40 students (53.3%) had negative attitudes and 68 students (90.7%) had high motivation. The results of statistical tests obtained p <? = 0.034 <0.05, then H0 is rejected and Ha is accepted, then there is a correlation attitude and motivation in providing first aid traffic accidents to students at SMK Negeri 1 Maumere. The results of this study are expected so that students can improve attitudes and motivation by increasing the information they have about first aid in traffic accidents. The school to be able to work with health services to hold a first aid simulation on an accident.